Analysis of Plastic Box Girder Bridge with Twin Box Cross Sections - Yuslinda, Yuslinda (Fakultas Teknik Universitas Tanjungpura, 2026)
In conventional steel bridge design, the material stress–strain response is often idealized as bilinear, neglecting strain hardening and potentially underestimating plastic capacity. This study investigates the influence of strain hardening on the plastic behavior of a plastic box girder bridge with twin box cross-sections. A 40 m span bridge with a total width of 10 m was analyzed using SAP2000 v15, following RSNI T-03-2005 for design provisions and RSNI T-02-2005 for loading. Two constitutive models were compared: a bilinear model and a strain-hardening model. The evaluation focused on the moment–curvature response, plastic moment, the extent of the inelastic region, and the shape factor. Results show that incorporating strain hardening increases the plastic moment from 171,000 kNm to 223,000 kNm, corresponding to a 23.32% enhancement. Moreover, the predicted length of the inelastic region increases by approximately 2.5 times relative to the bilinear assumption. These findings confirm that strain hardening substantially improves flexural capacity and ductility, highlighting the importance of realistic material modeling in plastic bridge analysis.